Theoretical and Practical Assessments of Transfer Prices. Legal Evidence From Romanian Case Law - Dumiter, Florin Cornel; Jimon, Ștefania Amalia (Journal of Legal Studies, 2020)
Transfer pricing represents the mainstream agenda in the light of tax law, lato sensu, and international taxation, stricto sensu. At the international level, there can be an emphasis on several problems related to taxation: double taxation, double non – taxation, permanent establishment, business profits, residence criteria, arm’s length principle, mutual agreement procedure, dispute resolution of tax conflicts. However, the problem of transfer pricing has more profound judicial and economic implications. The main objective of this paper is to evaluate and assess the underlying features and characteristics of transfer prices in the economical and judicial actual context. The operational objectives are related to a quid pro quo analysis regarding the fine-tuning aspects of transfer pricing in the digital taxation era. The case law presented in this article tackles the main problems of applying transfer pricing international regulation upon Romanian tax jurisprudence. The conclusion of this article highlights the need, mutadis mutandis, for a tax policy agenda revealing a strengthened fiscal and financial environment towards the creation of a new proper fiscal space.